Keeping People Safe Online – Fundamental Rights Protective Alternatives to Age Checks - Windwehr, Svea (Electronic Frontier Foundation, 2025)
This is the final part of a three-part series about age verification in the European Union. In part one, we give an overview of the political debate around age verification and explore the age verification proposal introduced by the European Commission, based on digital identities.